2015
DOI: 10.1631/jzus.b1400150
|View full text |Cite
|
Sign up to set email alerts
|

Assessing winter oilseed rape freeze injury based on Chinese HJ remote sensing data

Abstract: Abstract:The winter oilseed rape (Brassica napus L.) accounts for about 90% of the total acreage of oilseed rape in China. However, it suffers the risk of freeze injury during the winter. In this study, we used Chinese HJ-1A/1B CCD sensors, which have a revisit frequency of 2 d as well as 30 m spatial resolution, to monitor the freeze injury of oilseed rape. Mahalanobis distance-derived growing regions in a normal year were taken as the benchmark, and a mask method was applied to obtain the growing regions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Combined with indicators of a potential agricultural disaster such as extreme temperature, these data can improve the ability to predict the development and spatial distribution of damage caused by cold [5,46], freezing [7] or high temperatures [6]. In addition, the growth degree days (GDD), an important indicator for the cropping system in a region, can be calculated with high spatial-temporal daily mean air temperature data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with indicators of a potential agricultural disaster such as extreme temperature, these data can improve the ability to predict the development and spatial distribution of damage caused by cold [5,46], freezing [7] or high temperatures [6]. In addition, the growth degree days (GDD), an important indicator for the cropping system in a region, can be calculated with high spatial-temporal daily mean air temperature data.…”
Section: Discussionmentioning
confidence: 99%
“…Air temperature is an important parameter of the climate system and useful for a wide range of agriculture applications, including crop growth simulation [1,2], yield prediction [3,4], estimation of heat accumulation during the growing season [5], assessment of high-temperature damage [6], evaluation of crop freeze injury [7,8], and crop insect development prediction [9]. Currently, near-surface temperature data is collected by meteorological stations, and although such measurements offer the advantage of high accuracy and temporal resolution, their spatial resolution may be low and they may not adequately represent surface temperatures in areas with rugged or heterogeneous surfaces [10].These limitations can bias estimates of the spatial distribution of air temperature, even when researchers use advanced spatial interpolation methods [11].With the development of remote sensing technology, it has become possible to use thermal images from satellites to obtain land surface temperatures (LSTs) over wide areas, and this data can be used to instantaneously estimate spatially contiguous air temperatures [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the improvement of accuracy and robustness, the unsupervised CSRA method greatly improved the mapping efficiency due to its automatic ability. OR is one of the most important winter crops of China, especially in the Yangtze River Basin [11,16,17,48]. Compared with traditional methods, monitoring the spatial and temporal distributions of OR at the large-regional scale by satellite remote sensing can provide detailed spatial distributions and near real-time information, which is significant for agricultural agencies to monitor crop planting patterns, maintaining cropland utilization and soil fertility, gaining sufficient food, etc.…”
Section: Significance Uncertainty Analysis and Implications For Extmentioning
confidence: 99%
“…She et al [10] found the special movement of the red edge of OR from its original position towards the blue band direction during the flowering period to the pods period and applied to extract OR based on Hyperion imagery. However, the shortages of small spatial coverage, as well as expensive cost of hyperspectral images, limit its application on regional OR mapping.The second category mainly applies supervised classification methods on multispectral images during the flowering period to identify and extract OR at the local scale, since the flowering period is the best phenology stage of identifying OR from other crops [11]. As a member of the Brassicaceae family, OR appears as bright-yellow flowers lasting 30 days (approximately a quarter of its entire growing season) [3,12], which leads to a large difference on the reflectance at green, red, and near-infrared bands when compared with other crop species during the same period because of the radiation reflected by the flower petals [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation